A GUIDELINE OF BUDGET ADMINISTRATION ACCORDING TO GOOD GOVERNANCE SCHOOLS UNDER THE SECONDARY EDUCATIONAL SERVICE AREA OFFICE NAKHON SI THAMMARAT - Preecha, Patcharin; Weeraponkan, Boonlert; Yotarak, Maliwant (Journal of MCU Nakhondhat, 2023)
The objectives of this research were to 1) study the state of budget administration of schools under the secondary educational service area office Nakhon Si Thammarat 2) study budget management guidelines according to the principles of good governance of schools under the secondary educational service area office Nakhon Si Thammarat 3) present budget management guidelines according to good governance for secondary schools under the secondary educational service area office Nakhon Si Thammarat. The study was a qualitative research regulation. data were collected through in-depth interviews 15 key informants, study and outline guidelines through in-depth interviews 5 experts, and 7 competent persons in a group discussion. The results of the study revealed that: 1) The state of budget administration of schools under the secondary educational service area office Nakhon Si Thammarat: there are 7 steps in operation, consisting of 1) budget preparation and proposal 2) budget allocation 3) inspection, monitoring, evaluation and reporting on the use of funds and performance results 4) mobilizing resources and investment for study 5) financial management, 6) accounting management, and 7) supplies and asset management. some actions are not in accordance with the process and still need to be modified. 2) Guidelines for budget management of schools under the secondary educational service area office Nakhon Si Thammarat: there are 7 steps in operation, consisting of 1) budget preparation and proposal 2) budget allocation 3) inspection, monitoring, evaluation and reporting on the use of funds and performance results 4) mobilizing resources and investment for Study 5) financial management, 6) accounting management, and 7) supplies and asset management. Every step is carried out using good governance principles. 3) The experts examined the budget management guidelines of schools under the secondary educational service area office Nakhon Si Thammarat and found that everyone agreed that they were appropriate, beneficial, and applicable.